Oretta Zanini de Vita and Maureen B. Fant: Sauces & Shapes, Pasta the Italian Way - Riley, Gillian (Petits Propos Culinaires, 2014)
Oretta Zanini de Vita and Maureen B. Fant: Sauces & Shapes, Pasta the Italian Way: W. W. Norton & Company, 2013: 400 pp., hardback, $35.